2022
DOI: 10.1002/pd.6131
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of non‐invasive prenatal testing within a national UK antenatal screening programme: Impact on women's choices

Abstract: Objective To evaluate the implementation of non‐invasive prenatal testing (NIPT) on pregnant women's choices in a national NHS antenatal screening programme for Down's syndrome, Edwards' syndrome and Patau's syndrome. Method An observational study of all pregnant women with a singleton pregnancy and higher chance (≤1:150) combined or quadruple screening result from 30 April 2018 to 25 September 2020 in Wales, UK. Pregnant women's journey through the pathway was determined including uptake of NIPT, performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Recently, as NIPT has become more widespread, a method of combining multiple tests has been reported. [19][20][21][22] In the UK, a method of incorporating NIPT into a highly accurate first-trimester morphological screening using US by certificates sonographers and serum marker testing is being explored. 20,22,23 Their method can be available after the consolidation of pregnant women, while in a country where antenatal checkup by obstetricians is provided only a few times during the pregnancy, and this method is currently not compatible in a country like Japan, where small facilities are dispersed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, as NIPT has become more widespread, a method of combining multiple tests has been reported. [19][20][21][22] In the UK, a method of incorporating NIPT into a highly accurate first-trimester morphological screening using US by certificates sonographers and serum marker testing is being explored. 20,22,23 Their method can be available after the consolidation of pregnant women, while in a country where antenatal checkup by obstetricians is provided only a few times during the pregnancy, and this method is currently not compatible in a country like Japan, where small facilities are dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In the UK, a method of incorporating NIPT into a highly accurate first-trimester morphological screening using US by certificates sonographers and serum marker testing is being explored. 20,22,23 Their method can be available after the consolidation of pregnant women, while in a country where antenatal checkup by obstetricians is provided only a few times during the pregnancy, and this method is currently not compatible in a country like Japan, where small facilities are dispersed. In contrast, a study 24 conducted in Kumamoto, Japan, showed a scheme in which pregnant women who wanted prenatal genetic testing were first offered nuchal translucency US only, and then NIPT was suggested, if required, based on the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the introduction of NIPT for aneuploidy testing it was thought that the need for invasive diagnostic testing would decline very sharply; indeed, there has been a drop in CVS and amniocentesis procedures at fetal medicine units (FMUs), and studies have consistently shown that the majority of women with a high-chance screening result are more likely to opt for NIPT rather than invasive testing. 1 But NIPT cannot replace the need for evidence-based pretest and post-test counselling or accurate ultrasound scanning. Women with a raised nuchal translucency thickness in the first trimester need to be advised that the fetus not only has a higher risk of trisomy but is also at an increased risk of other genetic disorders that cannot be accurately tested for by NIPT, and may instead be amenable to prenatal diagnosis with a needle test (CVS/amniocentesis) and subsequent chromosomal microarray analysis, or exome sequencing (ES).…”
Section: The Needle and The Damage Donementioning
confidence: 99%
“…With new paradigms come new potential problems. After the introduction of NIPT for aneuploidy testing it was thought that the need for invasive diagnostic testing would decline very sharply; indeed, there has been a drop in CVS and amniocentesis procedures at fetal medicine units (FMUs), and studies have consistently shown that the majority of women with a high‐chance screening result are more likely to opt for NIPT rather than invasive testing 1 …”
Section: The Needle and The Damage Donementioning
confidence: 99%